2017
DOI: 10.3390/su9122136
|View full text |Cite
|
Sign up to set email alerts
|

Regional Economic Resilience: Resistance and Recoverability of Resource-Based Cities during Economic Crises in Northeast China

Abstract: This paper quantitatively analyzes the economic resilience of resource-based cities (RBCs) in Northeast China in terms of resistance and recoverability during two economic crises: the Asian financial crisis and the global financial crisis. Moreover, it analyzes the main factors that affected regional resilience. There are three main findings. First, the RBCs in general demonstrated poor resistance during both recessions, but there were variations among the different types of RBCs. Petroleum and metal cities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 47 publications
1
39
0
Order By: Relevance
“…The results showed that RBCs had low resistance during the two recessions from peak to trough, which was consistent with previous research on the economic resistance of RBCs in Northeast China (Tan et al, 2017), and is also consistent with other previous research by Li, Zhang, and Cheng (2009) and Su, Zhang, and Li (2008) who found that the economies of mining cities are vulnerable to external shocks, especially the resource-depleted mining cities. We found that coal-based and forestry-based cities had lower economic resistance, while oil & gas-based cities had high resistance.…”
Section: Economic Resilience Characteristic Of Rbcs In Chinasupporting
confidence: 92%
See 2 more Smart Citations
“…The results showed that RBCs had low resistance during the two recessions from peak to trough, which was consistent with previous research on the economic resistance of RBCs in Northeast China (Tan et al, 2017), and is also consistent with other previous research by Li, Zhang, and Cheng (2009) and Su, Zhang, and Li (2008) who found that the economies of mining cities are vulnerable to external shocks, especially the resource-depleted mining cities. We found that coal-based and forestry-based cities had lower economic resistance, while oil & gas-based cities had high resistance.…”
Section: Economic Resilience Characteristic Of Rbcs In Chinasupporting
confidence: 92%
“…Li, Zhang, and Li () examined regional economic resilience of Liaoning Province in China in terms of resistance and recoverability. Tan et al () quantitatively analyzed the economic resilience of RBCs in Northeast China in terms of resistance and recoverability. They draw the familiar conclusion that the regional economic resilience was low and its economy was more vulnerable to external shocks in Chinese old industrial cities and RBCs.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Community resilience and adaptive capacity have been studied within many disciplines, including ecology, disaster management, and community development [7][8][9]. However, the significance of resilience as a new strategy and path to the sustainable development of tourism communities has recently begun to attract the attention of tourism scholars [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…GeoDetector explores the consistency of the spatial distribution between independent variables and dependent variables on the basis of spatial heterogeneity and is mainly used to analyze impact factors of phenomena and interactions between factors [36]. GeoDetector is a novel tool for the exploratory analysis of spatial data, it has been widely applied to regional economy, population geography, planning, archeology and urbanization [37][38][39][40].…”
Section: Methodsmentioning
confidence: 99%